PENGARUH METODE MENGAJAR, MEDIA PEMBELAJARAN DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR SISWA SMA NEGERI 1 PLEMAHAN - Fedrianto, Andri; Sari, Yuli Ifana; Ni’matullah, Onik Farida (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2025)
This study aims to analyze the influence of teaching methods, learning media, and learning motivation on student learning achievement at SMA Negeri 1 Plemahan. The research method used is a quantitative approach with a correlational design. Data was collected through questionnaires given to students regarding their perceptions of the teaching methods and learning media used, as well as their level of motivation to learn. In addition, student learning achievement data is obtained from academic grades recorded in school documentation. The results of the analysis using multiple linear regression showed that teaching methods, learning media, and learning motivation had a significant influence on student learning achievement, with learning motivation as the most dominant variable. These findings provide insight into the importance of the right combination of teaching methods, the use of innovative learning media, and providing strong motivation to improve student learning achievement in secondary school.